Design, synthesis and preliminary biological studies of pyrrolidine derivatives as Mcl-1 inhibitors. Issue 24 (15th December 2015) - Wan, Yichao; Wang, Junhua; Sun, Feng'e; Chen, Minglu; Hou, Xuben; Fang, Hao
Graphical abstract: Abstract: Anti-apoptotic proteins, such as B-cell lymphoma (Bcl-2) protein, myeloid cell leukemia sequence 1 (Mcl-1) protein, are potential targets for cancer treatment. In the studies, a series of pyrrolidine derivatives were developed as potent Mcl-1 inhibitors. The preliminary biological studies suggested that most of target compounds exhibit good abilities for targeting Mcl-1 protein. Among them, compound21 ( K i  = 0.53 μM) exhibited equal inhibitory activities towards Mcl-1 protein compared to positive control gossypol ( K i  = 0.39 μM). This compound also possessed good antiproliferative activities against MDA-MB-231 and PC-3 cancer cells.